Multifractal-based assessment of Gilsocarbon graphite microstructures. (November 2016) - Vertyagina, Yelena; Marrow, Thomas James
Abstract: Three-dimensional X-ray tomographs of the microstructures of virgin and radiolytically oxidised polygranular Gilsocarbon nuclear graphite have been analysed with a multifractal approach, to consider the evolution of the porous structures of the filler particles and matrix regions. Correlations between the Rényi dimensions and structural parameters such as the total porosity, elastic modulus, and pore sizes have been revealed. The multifractal analysis has been used to develop an algorithm to detect the spatial distribution of filler particles, which has been applied to analyse the effects of filler particles on a crack path. Graphical abstract: